The world of Delacroix, 1798-1863 - Prideaux, Tom.; Time-Life Books (New York Time, 1981)
A profusely illustrated account of the life, career, works and times of Eugene Delacroix, master 19th century French painter, with background information on other artists of the time.
The Great Romantic -- Scattering the Rainbow -- An English Journey -- The Literary Bacchanal -- Morocco: A Fateful Interlude -- The Painter Comes of Age -- A Time for Masterworks -- The Final Encounter.
Fourth printing. Revised 1981
Includes bibliographical references (p. 192-193) and index.
Also issued online.
Keywords: Delacroix, Eugáene -- 1798-1863.